The pseudogene DUXAP10 contributes to gefitinib resistance in NSCLC by repressing OAS2 expression - Ren Shengnan; Zhu Ya; Wang Siying; Zhang Qinqiu; Zhang Niu; Zou Xiaoteng; Wei Chenchen; Wang Zhaoxia (Acta Biochimica et Biophysica Sinica, 2022)
Gefitinib, an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI),is the currently recommended first-line therapy for advanced EGFR-mutant lung cancer, and understanding the mechanism of resistance is the key to formulating therapeutic strategies for EGFR-TKIs. In this study, we evaluate the expression patterns and potential biological functions of the pseudogene DUXAP10 in gefitinib resistance. We find that pseudogene DUXAP10 expression is significantly upregulated in NSCLC gefitinib-resistant cells and tissues. Gain and loss of function assays reveal that knockdown of DUXAP10 by siRNA reverses gefitinib resistance both in vitro and in vivo. Furthermore, DUXAP10 interacts with the histone methyltransferase enhancer of zeste homolog 2 (EZH2) to repress the expression of 2′,5′-oligoadenylate synthetase (OAS2). Overall, our study highlights the pivotal role of DUXAP10 in gefitinib resistance, and the DUXAP10/EZH2/OAS2 axis might be a promising therapeutic target to overcome acquired gefitinib resistance in NSCLC.